Postantibiotic effects and postantibiotic sub-MIC effects of ciprofloxacin, pefloxacin and amikacin on the biological properties of Salmonella strains - Majtán, V; Majtánová, L (Folia microbiologica, 1997)
The postantibiotic effect (PAE) and the postantibiotic sub-MIC effect (PASME) of ciprofloxacin, pefloxacin and amikacin were studied for Salmonella typhimurium and S. enteritidis strains. PAE was induced by 2 x and 4 x MIC of antibiotics studied for 0.5 h. After PAE and PASME their effect on prophage induction of a lysogenic S. typhimurium strain and on Congo red binding for both strains as a marker of their surface hydrophobicity was examined. The longest PAE was found after treatment with ciprofloxacin, higher values being observed with S. typhimurium. PAEs of pefloxacin and amikacin were much lower, except for the suprainhibitory concentration 4 x MIC of amikacin with S. enteritidis (6.9h). PASMEs of ciprofloxacin did not allow any regrowth of either strain. For other antibiotics the PASMEs were different while concentrations of 2 x MIC + 0.2 x MIC and 0.3 x MIC, and of 4 x MIC + 0.1 x MIC, 0.2 x MIC and 0.3 x MIC of amikacin did not allow any regrowth of S. enteritidis. PAEs of the antibiotics tested did not affect the Congo red binding by both Salmonella strains, but the PAEs of ciprofloxacin and pefloxacin expressively induced a prophage of lysogenic S. typhimurium strain. We noted the influence of Congo red binding after applying 4 x MIC + 0.1 x MIC, 0.2 x MIC and 0.3 x MIC of amikacin for S. typhimurium and 2 x MIC + 0.1 x MIC for S. enteritidis.
Keywords: Microbial Sensitivity Tests; Coloring Agents; amikacin; pefloxacin; Salmonella enteritidis; Salmonella Phages; Virus Activation; fyzikální chemie; Kongo červeň; Dose-Response Relationship, Drug; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; antibakteriální látky; ciprofloxacin; Pefloxacin; Chemical Phenomena; Anti-Bacterial Agents; Bacteriophages; fágy salmonel; Salmonella typhimurium; barvicí látky; Ciprofloxacin; Chemistry, Physical; Congo Red; buněčná stěna; chemické jevy; vztah mezi dávkou a účinkem léčiva; bakteriofágy; Amikacin; Cell Wall; aktivace viru